Gender Equality and Inclusive Growth in Developing Asia - Yoko Niimi (Asian Development Bank (ADB), 2009)
This paper reviews the recent progress toward gender equality in developing Asia by examining a number of indicators proposed under the Millennium Development Goal 3 plus approach, focusing on gender inequalities in education and health outcomes (capability) and in labor market and political participation (access to resources and opportunities). Despite the improvement observed in education and, to a lesser extent, in health, the paper finds that women's improved capabilities do not seem to have been translated into an equal participation between men and women in economic and political activities. Further, it finds that gender gaps in almost all aspects reviewed remain significant, particularly in South Asia with some exceptions. A survey of empirical literature suggests that prevalence and persistence of gender inequality are often caused and reinforced by interlinked cultural, social, and economic factors. Empirical evidence also suggests that gender inequality is greater when a country's economic opportunities are more limited or households are in greater economic hardship. In conclusion, the paper argues that along with efforts in removing cultural, social, and institutional obstacles by educating the public and introducing/enforcing antidiscrimination legislations, promoting economic development to generate economic opportunities and improving women's capabilities and access to the opportunities are the key ingredients of a policy package for greater progress toward gender equality and inclusive growth in developing Asia.
hdl:11540/2571
Keywords: 330; gender equality; inclusive growth; Millennium Development Goals; Asia and the Pacific